Disclosures of voluntary accounting ratios and share price volatility: evidence from bursa Malaysia / Ahmad Hafiz Zainal Abidin - Zainal Abidin, Ahmad Hafiz (2011)
Accounting ratios are tools used by analyst to analyse the financial performance and position of a company. The presence of accounting ratios in annual reports would enhance the understandability and analytical concerns of the financial statements. This features are important to the users of financial statements especially stakeholder who relies on financial statements to value a firm. However, the disclosures of accounting ratios in an annual report among listed companies in Bursa Malaysia were found to be relatively low in Malaysia. This thesis examines the disclosures of accounting ratios in annual reports towards the volatility of share prices. To indicate the usefulness of accounting ratios to the investors, the volatility of share prices are measured (by means of standard deviation) which represent the level of trading activities took place during the announcement period. These volatilities of share prices are then analysed to find its correlation with the level of accounting ratios disclosed by the companies in their annual reports. Samples are collected from 50 companies listed in Bursa Malaysia during 2008 and 2009. This thesis provides evidence that the disclosures of accounting ratios in an annual report are significantly influence the volatility of share prices in the market. These findings conclude that the disclosures accounting ratios in an annual report would make the issued shares of a company more attractive to the investors in market.